Diethyl 5-amino-2,4,6-triiodoisophthalate - Wu, Jun (International Union of Crystallography, 2009)
The title compound, C(12)H(12)I(3)NO(4), crystallizes with two molecules in an asymmetric unit. In one of the molecules, the conformation of the O—C—O—C in one ester group is cis and trans in the other. The corresponding conformations for both the ester groups in the other molecule are trans. The I atoms and the benzene rings in the two molecules are approximately coplanar, the I atoms deviating by 0.219 (14), 0.056 (15) and −0.143 (14) Å from the mean plane of the benzene ring in one molecule and 0.189 (14), −0.162 (15) and −0.068 (14) Å in the other. The planes of the ester groups are almost orthogonal to those of the benzene rings in both molecules, forming dihedral angles of 88.1 (4), 72.2 (4), 73.0 (4) and 86.6 (4)°. The mean planes of the benzene rings in the two molecules are inclined at 74.6 (4)° with respect to each other. In the crystal, intermolecular I⋯O interactions [3.138 (7) and 3.144 (7) Å] link the molecules into infinite chains along the a axis. In addition, non-classical C—H⋯O hydrogen bonds are observed.